The developmental psychopathology of alcohol use and alcohol disorders: Research achievements and future directions. (17th December 2013) - Chassin, Laurie; Sher, Kenneth J.; Hussong, Andrea; Curran, Patrick
Abstract: The last 25 years have seen significant advances in our conceptualization of alcohol use and alcohol use disorders within a developmental framework, along with advances in our empirical understanding that have been potentiated by advances in quantitative methods. These include advances in understanding the heterogeneity of trajectories of alcohol outcomes; new insights about early childhood antecedents, and adolescence and emerging adulthood as important developmental periods for alcohol outcomes; a more nuanced understanding of the influences of developmental transitions, and their timing and contexts; a greater appreciation for the importance of considering multiple levels of analysis (including an increasing number of genetically informative studies); a continuing focus on studying multiple pathways underlying alcohol outcomes; and an increasing focus on studying the effects of alcohol exposure on future development. The current paper reviews these advances and suggests directions for future study.